DAKWAH DAN GERAKAN ANTI ISLAM (Membendung Gerakan Anti Islam Melalui Dakwah Berdimensi Kerahmatan) - Muhammad Thahir (KOMUNIDA : Media Komunikasi dan Dakwah, 2017)
A new phenomenon that emerged among the fobian, where Islam is regarded as the most dangerous enemy. Phobia against Islam (Islamophobia) is a propaganda of the anti-Islam movement that was born since the WTS event in the US, where Islam is the target of suspicion as a religion that teaches violence and terrorist nests.